Pengaruh Green Marketing Dan Sosial Media Marketing Terhadap Keputusan Pembelian Konsumen Produk Jajanan Khas Bima - Putra, Wanda Di; ErnawatI, Sri; Widakdo, Sugeng (ProBisnis : Jurnal Manajemen, 2024)
Industrial developments are changing a person's purchasing decision process, currently, Social Media Marketing is the basis of reference in purchasing, as is Green marketing. The aim of this research is to determine the influence of Green marketing and social media marketing on purchasing decisions, both partially and simultaneously. The type of research is associative. The research instrument uses a questionnaire with a Likert scale. The population used in this research is all consumers who have purchased bima snack products whose exact number is not known (unknown population). The number of samples used in this research was 50 respondents with a sampling technique, namely purposive sampling. Data collection techniques using observation, questionnaires, and literature study. Data analysis techniques by carrying out validity tests, reliability tests, multiple linear regression tests, correlation coefficients, determination tests, t tests, and f tests. The results of this research show that Green marketing has a significant effect while social media marketing does not have a significant effect on purchasing decisions, while simultaneously Green marketing and social media marketing have an effect on purchasing decisions